Segmental spring Untuk Koreksi Single Crossbite Pada Pasien Klas IV Kennedy (Case Report) - zulfan, zulfan; Simangunsong, Steffi Margaretha; Anastasia, Irene (Prima Journal of Oral and Dental Sciences, 2019)
Anterior crossbite is a malocclusion that is often found and must be treated immediately to prevent damage to tooth enamel later. In this case the anterior crossbite occurs in the upper canine against the lower canine where the condition is partly more that the maxillary teeth have been edentulous and replaced with removable partial dentures. Treatment is performed using segmental fixed orthodontics for correction of anterior crossbite. The treatment was completed in a relatively short time and only took 8 months and the patient was satisfied with the results of the treatment.